Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1089/cbr.2010.0896
|View full text |Cite
|
Sign up to set email alerts
|

The Radioprotective Effect of Zataria multiflora Against Genotoxicity Induced by γ Irradiation in Human Blood Lymphocytes

Abstract: The radioprotective effect of hydroalcholic Zataria multiflora (Avishan-e shirazi) extract was investigated against genotoxicity induced by γ irradiation in human lymphocytes. Peripheral blood samples were collected from human volunteers and incubated with Z. multiflora extract at different concentrations (5, 10, and 50 μg/mL) for 1 hour. At each dose point, the whole blood was exposed in vitro to 150 cGy of cobalt-60 γ irradiation, and then the lymphocytes were cultured with mitogenic stimulation to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 19 publications
1
84
0
Order By: Relevance
“…The radioprotective effect of Z. multiflora and constituents thymol against genotoxicity induced by γ‐irradiation in human blood lymphocytes indicated that Z. multiflora can reduce the genotoxicity induced by γ‐irradiation in human lymphocytes . It was shown that the chemoprotective and radioprotective effects of thymol vs. genotoxicity induced by chemical agent are mainly accompanied by its antioxidant activity .…”
Section: Resultsmentioning
confidence: 99%
“…The radioprotective effect of Z. multiflora and constituents thymol against genotoxicity induced by γ‐irradiation in human blood lymphocytes indicated that Z. multiflora can reduce the genotoxicity induced by γ‐irradiation in human lymphocytes . It was shown that the chemoprotective and radioprotective effects of thymol vs. genotoxicity induced by chemical agent are mainly accompanied by its antioxidant activity .…”
Section: Resultsmentioning
confidence: 99%
“…The control included a mixture of 2 ml of methanol and 2 ml of plant extract, and test/control was a sample including 2 ml of DPHH and 2 ml of plant extract/BHT at different concentrations . The experiment was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Butylated hydroxytoluene (BHT) was used as a positive control. Then, absorption of samples at 517 nm was measured by a spectrophotometer, and antioxidant activity level was determined by the following formula:…”
Section: Methodsmentioning
confidence: 99%